2015
DOI: 10.5223/pghn.2015.18.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Blood Urea Nitrogen/Creatinine Ratio in Gastrointestinal Bleeding with Melena in Children

Abstract: PurposeThe aims of our study were to evaluate the blood urea nitrogen to creatinine ratio (BUN/Cr ratio) for distinguishing between an upper and lower gastrointestinal bleeding (GIB), and differentiating between the two most common causes of upper gastrointestinal bleeding (UGIB) presenting with melena in children.MethodsRetrospective data of patients with GIB presenting with melena were analyzed. The data from 60 cases were reviewed including demographics, laboratory findings, diagnostic modalities and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…This result is consistent with a study that found no significant difference in Hb between upper and lower GIB in children. 30 However, in contrast to our study, several other studies in people have found that Hb, Hct, or both were significantly decreased in patients with upper GIB compared to those with lower GIB. 5,7,31 In these studies, it was postulated that upper GIB was more severe than lower GIB, resulting in more severe blood loss.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with a study that found no significant difference in Hb between upper and lower GIB in children. 30 However, in contrast to our study, several other studies in people have found that Hb, Hct, or both were significantly decreased in patients with upper GIB compared to those with lower GIB. 5,7,31 In these studies, it was postulated that upper GIB was more severe than lower GIB, resulting in more severe blood loss.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, Hb and Hct were not significantly different between dogs with upper and lower GIB. This result is consistent with a study that found no significant difference in Hb between upper and lower GIB in children 30 . However, in contrast to our study, several other studies in people have found that Hb, Hct, or both were significantly decreased in patients with upper GIB compared to those with lower GIB 5,7,31 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A BCR ratio of more than 30:1 is used to differentiate upper GI bleed from lower GI bleed in children. 17,18 This is because the transit time is higher in upper GI bleed, allowing more time for absorption and catabolism. 19 BCR was found to be significantly associated with severity of dehydration.…”
Section: Discussionmentioning
confidence: 99%